Sodium Cyclamate Identification and Determination of Dawet Ice Sold in Wedi District Indonesia - Makhabbah Jamilatun; Pradea Indah Lukito; Ira Dwi Astuti (University of Sultan Ageng Tirtayasa, 2022)
Sweeteners are food additives that are added to food or beverages to create a sweet taste, improve taste, aroma as well as a source of calories for the body. Sodium cyclamate is a sweetener food additive that is permitted to be used in food products but is often misused by food manufacturers. Excessive consumption of sodium cyclamate can cause bladder cancer, stomach pain, headache, and fever. This study aims to determine the content of sodium cyclamate in dawet ice sold in Wedi District. This study uses descriptive methods for both qualitative and quantitative. Identification of sodium cyclamate content in dawet ice sold in Wedi District using the precipitation test method, determination of sodium cyclamate content was determined quantitatively using UV-visible spectrophotometry. The results of the precipitation test showed that 5 positive samples contained artificial sodium cyclamate, with sodium cyclamate levels of 58.683 mg/L, 79.466 mg/L, 95.066 mg/L, 94.116 mg/L, and 79.5 mg/L, respectively. The conclusion is that the sodium cyclamate content in dawet ice sold in Wedi District from all samples analyzed does not exceed the maximum usage limit set by BPOM Regulation of the Republic of Indonesia No. 4 of 2014, concerning the Maximum Limit for the Use of Sweetener Food Additives, amounted to 250 mg/kg